Getting ahead : a communication skills course for business English with answers (Student's book) - Jones-Macziola, Sarah. (Tiếng Anh trong giao dịch thương mại., 2003)
Introductions and greetings; Occupations; Companies; The place of work; Revision and consolidation; ...